Effects of mood states and team identification on pricing in the secondary ticket market. Issue 3 (10th July 2017) - Ballouli, Khalid; Reese, Jason; Brown, Brandon
Abstract : Purpose: Although current literature offers support for understanding sport consumer behavior from psychological and sociological perspectives, there is a lack of research that examines the effect of one's emotional response to team outcomes on subsequent economic decisions. The purpose of this paper is to bridge this gap by studying how emotional responses to sport events moderate a typical endowment bias in the secondary ticket market. Design/methodology/approach: This research comprised a 3×2×2 between-participants design with emotional state (positive, negative, and neutral), role (seller, buyer), and fan identification (high, low) as the three factors. Prospect theory and social identity theory guided hypothesis development whereby it was proposed that, depending on the affective response of study participants to positive, negative, or neutral publicity concerning the team, team identification would impact the transaction function (buyers vs sellers) on price values for tickets to a future event. Findings: Findings revealed an interaction effect of emotions and team identification on the endowment effect to the extent that bargaining gaps between sellers and buyers increased or decreased depending on mood states and levels of identification with the team. Originality/value: This study adds to the literature on emotions and the key role they play in effecting pricing decisions and consumer behavior, especially given fan identification is such a significant area of study with numerous implications for sport business and management.